Hadith Criticism of Badal Hajj Perspective A. Hassan: Study of Takhrij and Syarah Hadith - Irwansyah, Ade; Nitiraharja, Muhammad Thoriq (Journal of Takhrij Al-Hadith, 2024)
This study aims to discuss the hadith about Badal Hajj. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about haji in the history of Bukhari No. 1417. The results and discussion of this study indicate that the quality of hadith status is authentic in Sanad, but dhaif in terms of Matan. This study concludes that the hadith narrated by Bukhari no 1417 cannot be used as evidence, because it contradicts the verses of the Qur'an, Hadith, the words of the companions of Ibn Abbas and Ibn Umar, as well as the words of the Tafsir Experts.